Awareness of Adult Basic Life Support among Graduates in a Medical College of Kathmandu - Dixit, Siddharth; Dahal, Sirjana; Dixit, Punam Basnet; Lama, Geshu (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Survival after sudden cardiac arrest depends upon early intervention, quality of cardiopulmonary resuscitation (CPR) and time of defibrillation. So, it is very important that at least the medical personnel know about Basic Life Support (BLS) as they are frequently facing the life threatening situations. Objective: To assess the level of awareness regarding adult basic life support among graduates in a medical college of Kathmandu. Methods: A descriptive cross-sectional study was conducted after ethical approval in Kathmandu Medical College and Teaching Hospital from April to September 2018 among 150 medical and dental graduates including interns and dental/medical officers. A structured self-administered questionnaire was used to assess their awareness regarding Adult BLS. Data were entered and analysed in Microsoft Excel Sheet. Mean, standard deviation, frequency, and percentage were calculated. Results: Most of the graduates surveyed (122, 81.3%) had heard about Adult BLS and felt the need to know about it (142, 94.7%). They felt the necessity including BLS training as a part of medical curriculum (144, 96%). Some of them (58, 38.7%) had seen BLS being done. However, very few (2, 1.3%) had actually done BLS on a patient. Some (54, 36%) had attended workshop on BLS. Conclusion: The findings of the study concluded that although most of the medical and dental graduates felt the need, very few had attended workshop for BLS. The BLS training should be included in the medical curriculum so that the graduates would be able to effectively manage the life-threatening emergencies.